Air Power as a Coercive Instrument - Byman, Daniel (RAND Corporation, 1999)
Coercion--the use of threatened force to induce an adversary to change its behavior--is a critical function of the U.S. military. U.S. forces have recently fought in the Balkans, the Persian Gulf, and the Horn of Africa to compel recalcitrant regimes and warlords to stop repression, abandon weapons programs, permit humanitarian relief, and otherwise modify their actions. Yet despite its overwhelming military might, the United States often fails to coerce successfully. This report examines the phenomenon of coercion and how air power can contribute to its success. Three factors increase the likelihood of successful coercion: (1) the coercer's ability to raise the costs it imposes while denying the adversary the chance to respond (escalation dominance); (2) an ability to block an adversary's military strategy for victory; and (3) an ability to magnify third-party threats, such as internal instability or the danger posed by another enemy. Domestic political concerns (such as casualty sensitivity) and coalition dynamics often constrain coercive operations and impair the achievement of these conditions. Air power can deliver potent and credible threats that foster the above factors while neutralizing adversary countercoercive moves. When the favorable factors are absent, however, air power--or any other military instrument--will probably fail to coerce. Policymakers' use of coercive air power under inauspicious conditions diminishes the chances of using it elsewhere when the prospects of success would be greater.